Distribution and population size estimation of the moor frog Rana arvalis Nilsson, 1842 in Ljubljansko barje Nature Park, central Slovenia - David Stanković; Maja Cipot (Natura Sloveniae)
Until recently, the moor frog Rana arvalis has been recorded only from the Pannonian and Sava Basins of north-eastern and south-eastern Slovenia, respectively. Here we report on the occurrence of the species at Ljubljansko barje, central Slovenia, and give estimates of the species’ abundance and distribution. In addition, we present some morphological characteristics of this population and offer insights into the present threats and the status of its habitats. The overall population size was estimated through egg mass count and is calculated to be more than 19,000 adults. All findings were distributed in two separate clusters. The northern cluster hosted more than 96% of all findings, while the smaller cluster in the south-eastern part of Ljubljansko barje accounted for only a fraction of the records. Even though the habitats in the northern cluster are relatively well preserved, the possibility of local extinction remains high owing to the immediate proximity of the capital and the municipal landfill site, which is planned for expansion in the near future.